Can historians influence public policy? Challenges and possibilities. Issue 1 (2nd January 2021) - Holbrook, Carolyn; Lowe, David
Abstract: This article examines the traditional divide between historical expertise and the world of policy making. It traces the origins of academic historians' reluctance to engage in present-day debates within the context of the development of the discipline, and claims that a quartet of pressing global issues – climate change, rising inequality, disenchantment with democratic governance and the Corona virus pandemic – present an opportunity for history to assert its relevance to the present. In arguing that the expertise of historians should be more effectively tapped to address significant environmental, economic, security, health and other issues, the article tracks the growth of policy history initiatives in Australia, the United States and Britain. It claims that greater and more explicit engagement with contemporary issues among scholars will provide the discipline of history with a stronger public presence, both within and outside the academy. This public demonstration of the value of history can be a defence against the hostility directed towards current humanities disciplines by political conservatives, including the incumbent Liberal-National government led by Scott Morrison. This article is concerned with the capacity for academic history to enlarge and contextualise public debates rather than conjure crude 'lessons' or quickly-drawn analogical templates. We encourage historians to communicate productively with governments and the broader realm of policy makers and shapers, and assist them to incorporate historical consciousness into their decision-making.